READING THE LORD’S PRAYER THROUGH EWE-GHANAIAN DEMONOLOGICAL LENS - E. van Eck; D. Sakitey (Acta Theologica, 2019)
This article examines the phrase ???? ????? ??ã? ??? ??? ??????? in Matthew’s rendition of the Lord’s Prayer through the Ewe-Ghanaian demonological lens. It employs a combination of the historical-critical and indigenous mother tongue biblical hermeneutics methods to address the ambiguity associated with the phrase ??? ??? ??????? in the petition. It also engages the world of the text with the Ewe-Ghanaian demonological world view and defines the place of ??????? (evil/evil one) in Ewe-Ghanaian Christian spirituality. The article discusses the various hermeneutical and theological positions on the text and juxtaposes them with popular Ewe-Ghanaian Christian demonology. The article argues that the aggressiveness with which the Ewe-Ghanaian Christian confronts his/her destiny issues is premised on the primal belief that everyone came to this world with his/ her own destiny (gbetsi) or fortune (aklama). However, there are forces  that interfere with one’s destiny. It is against this backdrop that one must relentlessly wage a spiritual warfare against those forces through not only tumultuous and verbose prayers, but also ritual  performances, in order to either protect a good fortune or reverse a bad one. The phrase ???? ????? ??ã? ??? ??? ??????? (Mat. 6:13b) is, therefore, a call on “Our Father in the heavens” to reverse any misfortune in one’s life, in order to fulfil one’s destiny in life.